Histopathological Study of Urinary Bladder Neoplasms - Jasmin Jasani; Gargi Joshi; Harsh Pandya (Institute of Medico-legal Publications Pvt Ltd, 2021)
Inroduction:- Urinary bladder tumor is the 7th most common tumor worldwide. Urinary bladder carcinomahas varying type of histological variants and complexity with an aggressive biological behaviour.Methods:- A total of 37 cases of urinary bladder neoplasia [histological proven] of patients admitted in atertiary care teaching hospital were studied retrospectively over the period from June 2019 - Oct 2020 in theDepartment of Pathology. On the basis of histology, these cases have grading by the means of WHO(2016)/ISUP classification.Result:- Out of 37 cases, male were more commonly affected (28 cases) than female (9 cases). A peak ageincidence of cases was in the 6th decade.Conclusion:- In our study, males (75.67%) are more frequently affected compared to females. The mostfrequent neoplastic findings in urinary bladder is invasive papillary urothelial carcinoma (75.66%).